A comparative study of antiplaque and antigingivitis effects of herbal mouthrinse containing tea tree oil, clove, and basil with commercially available essential oil mouthrinse - Shaila V. Kothiwale; Vivek Patwardhan; Megha Gandhi; Rahul Sohoni; Ajay Kumar (Wolters Kluwer Medknow Publications, 2014)
Background: The relatively safe nature and cost-effectiveness of herbal extracts have led to a resurgent interest in their utility as therapeutic agents. Therefore, this prospective, double-blind, randomly controlled clinical trial was designed to compare the antiplaque and antigingivitis effects of newly formulated mouthrinse containing tea tree oil (TTO), clove, and basil with those of commercially available essential oil (EO) mouthrinse. Materials and Methods: Forty patients were selected for a 21-day study period and randomly divided into two groups. The test group patients were given newly formulated herbal mouthrinse and the control group patients were given commercially available EO mouthrinse. The Plaque Index (PI), Gingival Index (GI), and Papillary Marginal Attachment (PMA) Index were recorded at baseline, 14 days, and 21 days. The microbial colony forming units (CFU) were assessed at baseline and 21 days. Results: Test group patients using herbal mouthrinse showed significant improvement in GI (0.16), PI (0.57), and PMA (0.02) scores. These improvements were comparable to those achieved with commercially available EO mouthrinse. However, the aerobic and anaerobic CFU of microbiota were reduced with the herbal mouthrinse (P = 0.0000). Conclusion: The newly formulated herbal mouthrinse and commercially available mouthrinse were beneficial clinically as antiplaque and antigingivitis agents. Newly formulated mouthrinses showed significant reduction in microbial CFU at 21 days. So, our findings support the regular use of herbal mouthrinse as an antiplaque, antigingivitis, and antimicrobial rinse for better efficacy.